Adherence to rivaroxaban versus apixaban among patients with non-valvular atrial fibrillation: Analysis of overall population and subgroups of prior oral anticoagulant users - McHorney, Colleen A.; Crivera, Concetta; Laliberté, François; Germain, Guillaume; Wynant, Willy; Lefebvre, Patrick (PloS one, 2018)
Medication non-adherence can result in poor health outcomes. Understanding differences in adherence rates to non-vitamin K oral anticoagulants (NOACs) could guide treatment decisions and improve clinical outcomes among patients with non-valvular atrial fibrillation (NVAF). To compare adherence to rivaroxaban and apixaban among the overall NVAF population and subgroups of prior oral anticoagulant (OAC) users (e.g., multiple comorbidities, non-adherence risk factors). Using healthcare claims from the Truven Health Analytics MarketScan (7/2012-7/2015), adult patients with ≥2 dispensings of rivaroxaban or apixaban ≥ 180 days apart with > 60 days of supply, ≥ 6 months of pre- and post-index eligibility, ≥ 1 atrial fibrillation diagnosis pre- or on the index date, and without valvular involvement were identified. Propensity-score methods adjusting for potential baseline confounders were used to create matched cohorts of rivaroxaban and apixaban patients. Adherence was assessed during the implementation phase using the percentage of patients with proportion of days covered (PDC) ≥0.8 at 6 months. Subgroups of patients with prior OAC use were evaluated; additional subgroups were identified and evaluated by Quan-Charlson Comorbidity index ≥2 and presence of non-adherence risk factors (i.e., mental disorders, stress, isolation, and rheumatoid arthritis). A total of 13,890 NVAF subjects were included in each of the 2 matched cohorts. All baseline characteristics were balanced between cohorts. At 6 months, significantly more rivaroxaban users were adherent to treatment compared to apixaban users (81.8% vs. 78.0%; absolute difference of 3.8%; p<.001). Rivaroxaban users had significantly higher adherence rates in all subgroups examined. Rivaroxaban users had consistently higher adherence rates than apixaban users overall and among all NVAF subgroups examined.